Applicability evaluation of plunger lift technology in shale gas wells - Fan, Yu; Xiang, Jianhua; Li, Bochun; Chen, Jiaxiao; Jiang, Mi; Yu, Fan (Frontiers in Energy Research, 2024)
The accumulation of liquid in gas wells is a common problem in the later stages of shale gas production. The plunger lift is currently one of the most economically effective methods for removing accumulated liquid in gas wells, but its applicability is not yet clear. This article analyzes the production characteristics of gas wells on-site and summarizes the key indicators for evaluating the plunger lift technology, including casing pressure changes, production changes, liquid column plunger height, tubing-casing pressure differential changes, and differential size of pressure relief. Combined with numerical simulation methods, a complete set of evaluation systems for judging, classifying, and evaluating the effectiveness of plunger lift technology is established, and an evaluation method for the applicability of plunger lift technology is proposed. Taking well Ning 216-H4 as an example, a comprehensive evaluation is made on whether the gas well is suitable for plunger lift based on the height of the liquid column above the plunger, the production effect under pressure, and the overall shut-in time. This method has important guiding significance for the further promotion and application of plunger lift technology in deep wells, directional wells, and horizontal wells to achieve efficient development of natural gas.